1977
DOI: 10.1111/j.1365-2427.1977.tb01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zinc on lotic plants

Abstract: The toxicity of zinc to Hormidium rivulare Kiitz. in laboratory culture media is decreased by rises in the levels of magnesium, calcium and phosphate, and increased by rises in pH and cadmium. Tiie effects of all these are sufficiently marked that they may be expected to liave considerable importance in the field. In contrast, assays with sodium, chloride and sulphate showed no detectable influence of these ions on zinc toxicity.When applied at higher concentrations, calcium was always more effective than magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Many studies support the hypothesis that metal toxicity is reduced in response to increases in P concentrations (Harding and Whitton 1977; Say and Whitton 1977; Chen 1994). On the other hand, several studies indicate that metals can induce nutrient limitation which can result in reduced algal growth (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Many studies support the hypothesis that metal toxicity is reduced in response to increases in P concentrations (Harding and Whitton 1977; Say and Whitton 1977; Chen 1994). On the other hand, several studies indicate that metals can induce nutrient limitation which can result in reduced algal growth (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Metal contaminants (zinc, copper, etc.) and the use of fertilizers and detergents containing phosphorus has been found to cause cumulative effects on cyanobacteria by inhibiting growth; although the presence of calcium and phosphate in the presence of metals has also been found to reduce their toxicity to cyanobacteria [44] [45]. Morphological effects of elevated copper include the production of sub-spherical rather than coccoid Synechococcus PCC 6301 [45] as well as the inhibition of photosynthesis in Nostoc calcicola [46].…”
Section: Resultsmentioning
confidence: 99%
“…Both toxicants and nutrients can play major roles in microbial population dynamics is important in natural aquatic ecosystems as well as in laboratory toxicity testing. Several studies have reported that metal toxicity on algae is affected by the phosphate concentration (Say and Whitton, 1977;Shehata and Whitton, 1982;Chen, 1994). Chen (1994) also demonstrated that the average tolerance of algal cells decreases with the concentration of phosphate.…”
Section: Introductionmentioning
confidence: 99%